2015
DOI: 10.1016/j.ecolind.2015.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Connecting soundscape to landscape: Which acoustic index best describes landscape configuration?

Abstract: a b s t r a c tSoundscape assessment has been proposed as a remote ecological monitoring tool for measuring biodiversity, but few studies have examined how soundscape patterns vary with landscape configuration and condition. The goal of our study was to examine a suite of published acoustic indices to determine whether they provide comparable results relative to varying levels of landscape fragmentation and ecological condition in nineteen forest sites in eastern Australia. Our comparison of six acoustic indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
157
0
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(197 citation statements)
references
References 46 publications
16
157
0
4
Order By: Relevance
“…In addition, to link the composition and dynamics of biophony with biological and ecological processes, ornithologists would bring valuable knowledge concerning species behavior, phylogenetic history, and ecology. Soundscape ecology would bring complementary knowledge about landscape contexts (Tucker et al 2014, Fuller et al 2015. Extensive, currently accessible soundscape libraries from which such data could be derived include those of the Center for Global Soundscapes (http://centerforglobalsoundscapes.org) and the REAL (Kasten et al 2012 Kasten et al (2012), may also have to be applied or developed in order for ornithologists to consider representative samples from any given dataset.…”
Section: Ornithological Contributions To the Future Of Soundscape Ecomentioning
confidence: 99%
“…In addition, to link the composition and dynamics of biophony with biological and ecological processes, ornithologists would bring valuable knowledge concerning species behavior, phylogenetic history, and ecology. Soundscape ecology would bring complementary knowledge about landscape contexts (Tucker et al 2014, Fuller et al 2015. Extensive, currently accessible soundscape libraries from which such data could be derived include those of the Center for Global Soundscapes (http://centerforglobalsoundscapes.org) and the REAL (Kasten et al 2012 Kasten et al (2012), may also have to be applied or developed in order for ornithologists to consider representative samples from any given dataset.…”
Section: Ornithological Contributions To the Future Of Soundscape Ecomentioning
confidence: 99%
“…The Normalized difference soundscape index (NDSI) has been shown to accurately reflect anthropogenic noise when values are low (Gage and Axel 2014), and avian species richness when values are high (Fuller et al 2015). We found that, on average, our urban site in Sueyoshi park had higher values than our suburban sites in Nago and Nakagusuku.…”
Section: Soundscape Indicesmentioning
confidence: 59%
“…Previous studies have found that ACI increases drastically in the presence of cicadas and other orthopterans that produce a broadband signal (Farina et al 2011;Fuller et al 2015). BioA was also highest at night in Nago and Nakagusuku, likely due to the persistent broadband signaling of several orthopteran species, especially Hexacentrus unicolor.…”
Section: Combining Approachesmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, to link the composition and dynamics of biophony with biological and ecological processes, ornithologists would bring valuable knowledge concerning species behavior, phylogenetic history, and ecology. Soundscape ecology would bring complementary knowledge about landscape contexts (Tucker et al 2014, Fuller et al 2015. Extensive, currently accessible soundscape libraries from which such data could be derived include those of the Center for Global Soundscapes (http://centerforglobalsoundscapes.org) and the REAL (Kasten et al 2012).…”
Section: Ornithological Contributions To the Future Of Soundscape Ecomentioning
confidence: 99%